Nanofibers of gelatin and polivinyl-alcohol-chitosan for wound dressing application: fabrication and characterization - Campa-Siqueiros,Paola (2020)
Abstract Electrospun nanofibers from gelatin (G), chitosan (CS), and chitosan-polyvinyl alcohol (CS-PVA) were developed by electrospinning process. Mechanical properties were determined by the tensile test, the elastic modulus values of the nanofibers were G (15.418-34.34 MPa) and CS-PVA (17.44-126.427 MPa). The morphological characterization by SEM revealed that the systems with 15% G and 6% CS-PVA showed morphological homogeneity. Structural characterization by FTIR indicated an interaction among some functional groups of the component. Thermal analysis by DSC and TGA showed degradation temperatures for G (330 °C), CS (210 °C to 370 °C), and PVA (310 °C to 420 °C). The contact angles values denoted the hydrophilic nature of the material. Finally, the antimicrobial assay proved that both 15% G and 7% PVA on the CS-PVA system presented the best antimicrobial effect. The results indicate that the electrospun nanofibers fabricated with G or CS-PVA can be used as wound healing dressings.